Further exclusion data for the Von Recklinghausen neurofibromatosis gene: a genetic linkage study of 19 polymorphic markers. - Upadhyaya, M (1987)
Linkage analysis on a panel of 15 Von Recklinghausen neurofibromatosis (VRNF) families with 19 polymorphic markers was carried out using the computer programme M-Link. Our findings have excluded VRNF from a significant proportion of the genome.